The Relations between Internet using as a Learning Media and the Interest in Learning of Guidance and Counseling Study Program Students - Nur Wisma; Faradillah Rahayu Metrin (JRTI (Jurnal Riset Tindakan Indonesia), 2022)
This quantitative descriptive research is an correlational, aiming to determine the relationship between the use of the internet as a learning medium and the learning interest of the 2018 students of the Guidance and Counseling study program at Sriwijaya University. The population in this study were 70 students and a sample of 64 students using proportional random sampling technique. The data collection instrument used a questionnaire using a Likert scale. The data analysis used was the product moment correlation. The results of the analysis obtained a correlation coefficient of 0.574 which indicates that the use of the internet as a learning medium with student interest in learning has a relationship with a rather low level of relationship at a significance level of 0.05. So it can be concluded that there is a relationship between the use of the internet as a learning medium and the interest in learning of students from the 2018 batch of the guidance and counseling study program FKIP Sriwijaya University.